2014
DOI: 10.5935/1808-8694.20140030
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic endonasal transsphenoidal resection of pituitary adenomas: preliminary evaluation of consecutive cases✩✩Please cite this article as: Chone CT, Sampaio MH, Sakano E, Paschoal JR, Garnes HM, Queiroz L, et al. Endoscopic endonasal transsphenoidal resection of pituitary adenomas: preliminary evaluation of consecutive cases. Braz J Otorhinolaryngol. 2014;80:146–51.,✩✩✩✩Study conducted at Department of Otolaryngology Head and Neck, Department of Neurosurgery, Centro Medico de Campinas Hospital, Depart

Abstract: Endoscopic endonasal pituitary surgery is a feasible technique, yielding good surgical and functional outcomes, and low morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…GTR was available for n=8257 patients (Table 3). Using the fixed-effect model, the pooled rate of GTR among all studies was 71.0% (95%CI: 69.9–72.1%, I 2 =91.2%; P-heterogeneity<0.01 under the fixed-effect model (Table 4) [411, 15, 16, 1823, 27, 3033, 35, 3739, 42, 44, 45, 47, 48, 5056, 59, 64, 68, 70, 71, 74, 75, 78, 80, 8284, 86–92]. When eTSS and mTSS were compared, GTR rate was significantly higher in eTSS (n=50 studies, GTR=74.0%, 95%CI: 72.6–75.3%, I 2 =92.1%; P-heterogeneity<0.01) than in mTSS (n=20 studies, GTR=66.4%, 95%CI: 64.5–68.2%, I 2 =84.0%; P-heterogeneity<0.01) (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…GTR was available for n=8257 patients (Table 3). Using the fixed-effect model, the pooled rate of GTR among all studies was 71.0% (95%CI: 69.9–72.1%, I 2 =91.2%; P-heterogeneity<0.01 under the fixed-effect model (Table 4) [411, 15, 16, 1823, 27, 3033, 35, 3739, 42, 44, 45, 47, 48, 5056, 59, 64, 68, 70, 71, 74, 75, 78, 80, 8284, 86–92]. When eTSS and mTSS were compared, GTR rate was significantly higher in eTSS (n=50 studies, GTR=74.0%, 95%CI: 72.6–75.3%, I 2 =92.1%; P-heterogeneity<0.01) than in mTSS (n=20 studies, GTR=66.4%, 95%CI: 64.5–68.2%, I 2 =84.0%; P-heterogeneity<0.01) (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-seven studies reported GTR for NFPA (n=2,655) [5, 7, 8, 11, 19, 20, 23, 32, 35, 45, 53, 56, 64, 78, 8890]. Under the fixed-effect model, the overall GTR rate for NFPA was 67.3% (95%CI: 65.3–69.2%, I 2 =87.7%, p-heterogeneity<0.01).…”
Section: Resultsmentioning
confidence: 99%
“…The complication rates of the previous endoscopic studies range from 10% to 26.3% and mortality rates of 0% to 0.68%. [ 19 , 26 , 35 37 ] The complications and mortality rate of microscopic transsphenoidal approach are 8.2–47% and 0–0.9%, respectively. [ 38 , 39 ] In our study, one patient with pituitary adenoma died in the postoperative period due to respiratory complications (mortality rate 0.69%), and none of the patients who were presented with pituitary apoplexy died after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…However, synechiae, anosmia, liquoric fistulas, 8 as well as lesions in noble structures, may cause irreversible damage. 9,10 Quality of life assessments and clinical follow-up of patients with chronic sinusopathy submitted to surgical treatment are considered the appropriate interventions to ensure that patients remain symptom-free for longer periods. 11 Knowing the anatomical references and fixed measurements with almost no variation in terms of gender, race, age, weight, and height might provide surgeons more reliability, minimizing complications and optimizing interventions in the nasal sinuses.…”
Section: Introductionmentioning
confidence: 99%